Phytotoxic Metabolites Produce by Fusarium oxysporum f. sp. cubense Race 2 - Portal González, N.; Soler, A.; Ribadeneira, C.; Solano, J.; Portieles, Roxana; Herrera Isla, L.; Companioni, B.; Borras-Hidalgo, Orlando; Santos Bermudez, Ramon (Frontiers in Microbiology, 2021)
Banana is a major tropical fruit crop but banana production worldwide is seriously threatened due to Fusarium wilt. Fusarium oxysporum f. sp. cubense (Foc), the causal agent of Fusarium wilt of banana (also referred as Panama disease) is an asexual, soil inhabiting facultative parasite. Foc isolates can be classified into three races that are not defined genetically, but for their pathogenicity to different banana cultivars. Despite mycotoxins being some of the best studied virulence factors of phytopathogenic fungi and these have been useful for the prediction of Foc virulence on banana plants, toxins produced by Foc race 2 strains have not been previously identified. The aim of this contribution was to identify the phytotoxic metabolites closely related to banana wilt caused by a Foc race 2 strain. We used an in vitro bioassay on detached banana leaves to evaluate the specificity of the microbial culture filtrates before a partial purification and further identification of Foc race 2 phytotoxins. A 29-days-old host-specific culture filtrate was obtained but specificity of culture filtrate was unrecovered after partial purification. The non-specific phytotoxins were characterized as fusaric acid, beauvericin and enniatin A. Whereas some, if not all, of these phytotoxins are important virulence factors, a proteinaceous fraction from the specific 29-days-old culture filtrate protected the leaves of the resistant banana cultivar from damage caused by such phytotoxic metabolites.